2018
DOI: 10.3389/fendo.2018.00497
|View full text |Cite
|
Sign up to set email alerts
|

Central Precocious Puberty in a Child With Metachromatic Leukodystrophy

Abstract: Metachromatic leucodystrophy (MLD) is a rare inherited lysosomal disorder caused by reduced activity of the enzyme arylsulfatase A with accumulation of sulfatides in the nervous system. We report a female child affected by MLD who developed central precocious puberty (CPP). This association has not been described so far. The proposita, after normal growth and psychomotor development, at age of 30 months presented with a rapidly progressive gait disturbance with frequent falls and with loss of acquired language… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
(37 reference statements)
1
6
0
Order By: Relevance
“…There are anecdotic reports of patients with precocious puberty in association with various inborn errors of metabolism (IEM) inducing accumulation of toxic substances in the central nervous system. Recently, a case of a girl with metachromatic leukodystrophy with puberty starting at 4 years, similar to our case, was reported [ 19 ]. CPP was also reported in a 4 year old girl with Tay-Sachs disease, in whom GM2 gangliosides storage was described in the hypothalamus post-mortem [ 20 ], in a few patients with mucopolysaccharidosis type IIIA [ 21 , 22 ] and in a patient with mucopolysaccharidosis type IH [ 23 ].…”
Section: Discussionsupporting
confidence: 75%
“…There are anecdotic reports of patients with precocious puberty in association with various inborn errors of metabolism (IEM) inducing accumulation of toxic substances in the central nervous system. Recently, a case of a girl with metachromatic leukodystrophy with puberty starting at 4 years, similar to our case, was reported [ 19 ]. CPP was also reported in a 4 year old girl with Tay-Sachs disease, in whom GM2 gangliosides storage was described in the hypothalamus post-mortem [ 20 ], in a few patients with mucopolysaccharidosis type IIIA [ 21 , 22 ] and in a patient with mucopolysaccharidosis type IH [ 23 ].…”
Section: Discussionsupporting
confidence: 75%
“…Cases of CPP have been documented in neurodegenerative diseases such as mucopolysaccharidosis type I [23] and type III [24], neuronal ceroid lipofuscinosis [12], metachromatic leukodystrophy late infantile form [25] and Beta-propeller protein-associated neurodegeneration (BPAN) [26], where accumulation of toxic metabolites in blood and brain is hypothesized as a triggering event for CPP. It is possible that CPP in these entities is coincidental, but the number of cases from different neurodegenerative diseases, some being very rare disorders, could indicate a causal relationship.…”
Section: Discussionmentioning
confidence: 99%
“…2 Accumulation of sulfatide in oligodendrocytes, Schwann cells, phagocytes, astrocytes, and lysosomes of neurons in cases of CPP in MDL causes demyelination and inflammatory changes that lead to apoptosis in the central and peripheral nerves, and in the white matter, thalamus, and basal ganglia of the brain. 4 Accumulation of autofluorescent storage material in lysosomes may have induced CPP in this case, although pathological evaluation was not done. Further investigation of the sites of accumulation and clinical symptoms of this disease is required.…”
mentioning
confidence: 88%
“…2 There are many possible causes of such lesions, including tumors, hypothalamic malformations, brain malformations, and trauma. 2 Lysosomal storage diseases (LSDs), such as mucopolysaccharidosis type III A, Hurler syndrome, Tay-Sachs disease, and heterozygous leukodystrophy (MDL) have also been reported as causes 1,[3][4] (Table S1). A literature review revealed 12 cases of LSD associated with CPP, including this case (seven boys, four girls, one unknown).…”
mentioning
confidence: 99%
See 1 more Smart Citation